2009
DOI: 10.1155/2009/707042
|View full text |Cite
|
Sign up to set email alerts
|

The Inflammatory Response to Miniaturised Extracorporeal Circulation: A Review of the Literature

Abstract: Conventional cardiopulmonary bypass can trigger a systemic inflammatory response syndrome similar to sepsis. Aetiological factors include surgical trauma, reperfusion injury, and, most importantly, contact of the blood with the synthetic surfaces of the heart-lung machine. Recently, a new cardiopulmonary bypass system, mini-extracorporeal circulation (MECC), has been developed and has shown promising early results in terms of reducing this inflammatory response. It has no venous reservoir, a reduced priming vo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
81
1
9

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(94 citation statements)
references
References 45 publications
(71 reference statements)
3
81
1
9
Order By: Relevance
“…This was based on the fact that the MoCA can be easily utilized in a busy clinical practice and enables health professionals to identify mild cognitive impairment through practical administration and interpretation steps. [5] Prolonged intensive care unit stay due to any reason, hemodynamic instability, and cerebrovascular event history were also among the exclusion criteria, which significantly limit the generalizability of our results to all patients undergoing cardiac surgery. In addition, ultrasonographic measurement of the gaseous micro-emboli at the entry of the venous site and way out of the arterial site might provide us more valuable results.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…This was based on the fact that the MoCA can be easily utilized in a busy clinical practice and enables health professionals to identify mild cognitive impairment through practical administration and interpretation steps. [5] Prolonged intensive care unit stay due to any reason, hemodynamic instability, and cerebrovascular event history were also among the exclusion criteria, which significantly limit the generalizability of our results to all patients undergoing cardiac surgery. In addition, ultrasonographic measurement of the gaseous micro-emboli at the entry of the venous site and way out of the arterial site might provide us more valuable results.…”
Section: Discussionmentioning
confidence: 98%
“…[4] Several strategies have been developed to minimize the entry of micro-bubbles into ECC, and to decrease the surface area as well as the prime volume. [5,6] New generation oxygenators with integrated arterial filters which allow the incorporation of arterial filters into the oxygenators have been reported to decrease cerebral injury through entrapment of the particulate matter and micro-bubbles. [7,8] Integration of arterial-line filters with oxygenators as a novel CPB design was contrived for integrating the concepts of "surface covering", "blood filtration", and "miniature".…”
mentioning
confidence: 99%
“…[17][18][19][20] Minimal extracorporeal circulation technology includes shorter tubes, which decreases PV. The additional benefits of such technology include a decrease in the coagulation cascade and a reduction in the need for blood transfusions in patients undergoing cardiac surgery.…”
Section: Discussionmentioning
confidence: 99%
“…The additional benefits of such technology include a decrease in the coagulation cascade and a reduction in the need for blood transfusions in patients undergoing cardiac surgery. [17][18][19][20] This technology should become more important and become even more popular in the future. However, our data suggested that the duration of CPB exposure is an important factor in eliciting the systemic inflammatory response in addition to blood contacting artificial surfaces.…”
Section: Discussionmentioning
confidence: 99%
“…These characteristics lead to a circuit prime volume smaller than standard ECC, ranging between 200-650 ml for the MECC against 1200-1600 ml for the standard ECC (Formica et al 2009Remady et al 2006). The combination of short length tubing, heparin pre-treatment, small size tubing and absence of a venous reservoir, leads to a significant reduction of hemodilution with as well as a reduction in clotting factor consumption ad triggering of SIRS (Vohra et al 2009;Ohata et al 2007;Wippermann et al 2005;Fromes et al 2002). The blood pump included in the circuit is usually a centrifugal pump.…”
Section: Anatomy Of the Miniaturized Extracorporeal Circulation Systemmentioning
confidence: 99%